PENGARUH PENDEKATAN HUMAN RELATIONS TERHADAP KINERJA PEGAWAI (Suatu Studi Pada Badan Kepegawaian Daerah Kabupaten Halmahera Barat) - Bethol, Iwan Christian; Kiyai, Burhanuddin; Kolondam, Helly (Sam Ratulangi University, 2016)
Abstrak: The research was conducted on the basis of initial observations location study indicated thatemployee performance is still relatively low. The relatively low performance of employees is presumablyrelated to the implementation of human relations factors in the work environment at the RegionalEmployment Board of West Halmahera. Thus, this study aims to: (1) to investigate the implementation ofhuman relations approach. (2) To determine the achievement of employee performance. (3) To analyze theeffect of the implementation of human relations approach to employee performance at the RegionalEmployment Board West Halmahera district. By applying the method of descriptive and quantitativeapproach, respondents were determined purposively sampled as many as 53 employees, then distributed alist of questions or the questionnaire, the results are tabulated and analyzed by applying statisticaltechniques. To describe the research variables used analytical technique that is processed in the percentageof Frequency Distribution Table, while to test the hypothesis used a simple linear regression analysis andcorrelation of product moment.Once the data is collected and then analyzed the results showed that (1) Implementation of human relationsapproach in working condition at the Regional Personnel Agency (BKD) West Halmahera has succeededin improving the performance of employees that are in the category of